Northern Sea Route: Transport, economy, geopolitics - Veretennikov N. P.; Bogahev V. F.; Ul'chenko M. V. (Vestnik MGTU, 2015)
The problems of the development of the Arctic region have been considered. The priorities of development of natural resources of the Arctic such as hydrocarbons and marine bioresources have been analyzed